2021
DOI: 10.1177/03000605211006597
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of immunological methods based on the singleplex and multiplex ImmunoCap systems for diagnosis of shrimp allergy

Abstract: Background Levels of specific IgE (sIgE) against allergen components can be assessed using multiplex assays or with highly sensitive, quantitative methods. The aim of this study was to compare the sensitivity and specificity of different immunological methods for diagnosis of shrimp allergy. Methods Twenty patients with positive skin prick tests for frozen tiger shrimp were selected for further examination. Blood samples were taken to assess concentrations of sIgE against the house dust mites Dermatophagoides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…This indicates that although component diagnostics based on the ImmunoCap ISAC test is important in assessing the allergen profile of patients, in the case of shrimp allergy, it plays an auxiliary role, and a negative result in the context of the allergen components Pen m 1, Pen m 2 and Pen m 4 does not rule out the shrimp allergy. In our previous research, we found that, in case of shrimp sensitization, the results of sIgE levels against corresponding allergen components determined using singleplex ImmunoCap (quantitative and highly sensitive) and ImmunoCap ISAC (semi-quantitative, multiplex micro-assay test) are similar in most cases, with correlations above 0.7 [22].…”
Section: Discussionmentioning
confidence: 86%
“…This indicates that although component diagnostics based on the ImmunoCap ISAC test is important in assessing the allergen profile of patients, in the case of shrimp allergy, it plays an auxiliary role, and a negative result in the context of the allergen components Pen m 1, Pen m 2 and Pen m 4 does not rule out the shrimp allergy. In our previous research, we found that, in case of shrimp sensitization, the results of sIgE levels against corresponding allergen components determined using singleplex ImmunoCap (quantitative and highly sensitive) and ImmunoCap ISAC (semi-quantitative, multiplex micro-assay test) are similar in most cases, with correlations above 0.7 [22].…”
Section: Discussionmentioning
confidence: 86%
“…The results were narratively synthesized. For consistency, data in the synthesis were limited to measurements with the conventional 32 , 33 , 34 cut‐off values of 0.35 kUA/l for ImmunoCAP and 0.3 ISU for ISAC. Meta‐analysis was not possible to perform, given the insufficient and disparate data.…”
Section: Methodsmentioning
confidence: 99%
“…ImmunoCAP detected elevated levels of shrimp sIgE in all patients. However, ISAC 112 indicated only a 50% detection rate against at least one out of three shrimp allergen components [ 123 ].…”
Section: Diagnosismentioning
confidence: 99%